O setor de defesa brasileiro no exterior: Desafios, oportunidades e subsídios para a revis\~ao dos documentos de defesa - Pedro Silva Barros; Raphael Camargo Lima; Paula Macedo Barros (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This paper aims to offer a panoramic view of the international performance of Brazilian defense sector. Based on an exploratory study from a new dataset, our goal is to analyze both the international performance of the Brazilian defense sector and the country's foreign military missions in the recent period. Additionally, the study offers a novel dataset to assess defense policy, support planning, and collaborate with democratic controls over the defense sector. The study's conclusion are as follows: i) there is a low political direction from the Brazilian Ministry of Defense on international missions; ii) there is a disproportionate concentration of interactions with the United States; iii) there is an imbalance in the emphasis on hemispheric institutions linked to the Organization of American States (OAS) in relation to other international institutions; iv) there is a growth of the regional interactions with Colombia, which overtook Argentina as the main destination for regional interactions; v) there was a relative increase in technical missions and military consultancies in Brazil's strategic surrounding countries; and vi) posts in companies and acquisition commissions are consistent with the main strategic defense programs and the origins of Brazilian defense equipment, but they must be improved. Finally, the study presents 14 public policy recommendations.
Keywords: F52; H56; N46; 330; defense; military; defense policy; international missions